2015
DOI: 10.1016/j.jana.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

“Is Your Man Stepping Out?” An Online Pilot Study to Evaluate Acceptability of a Guide-Enhanced HIV Prevention Soap Opera Video Series and Feasibility of Recruitment by Facebook Advertising

Abstract: Love, Sex, and Choices (LSC) is a 12-episode soap opera video series developed to reduce HIV risk among at-risk Black urban women. We added a video guide commentator to offer insights at critical dramatic moments. An online pilot study evaluated acceptability of the Guide Enhanced LSC (GELSC) and feasibility of Facebook© advertising, streaming to smartphones, and retention. Facebook© ads targeted high HIV-prevalence areas. In 30 days, Facebook© ads generated 230 screening interviews; 84 were high risk, 40 watc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Facebook, a popular social networking site (SNS) (2), offers advertising opportunities to vendors. Posting ads on Facebook has shown promise in recruiting target populations, particularly younger adults and adolescents to participate in research studies (3, 4) and to extend reach to geographically distant or otherwise harder to reach populations (5), such as, homeless populations, individuals concerned about the stigma of HIV, or those engaging in stigmatized behaviors. Recruitment of women, children, and people of color into clinical trials is a National Institutes of Health priority (6) so Facebook advertising could be a plausible approach to meeting recruitment goals.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Facebook, a popular social networking site (SNS) (2), offers advertising opportunities to vendors. Posting ads on Facebook has shown promise in recruiting target populations, particularly younger adults and adolescents to participate in research studies (3, 4) and to extend reach to geographically distant or otherwise harder to reach populations (5), such as, homeless populations, individuals concerned about the stigma of HIV, or those engaging in stigmatized behaviors. Recruitment of women, children, and people of color into clinical trials is a National Institutes of Health priority (6) so Facebook advertising could be a plausible approach to meeting recruitment goals.…”
Section: Introductionmentioning
confidence: 99%
“…Posting an ad on Facebook can be analogous to posting an ad for a study in the local paper. One clicks on a Facebook ad and is sent to a secured study website to review the full flyer, having left the Facebook platform (3). The use of Facebook advertising for research and program delivery is growing (5, 7), but, as identified by Pederson & Kurz (8), remains a relatively new area that requires further research and guidance into sample representativeness, protections of human subjects, and validity of the data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations